Faktor-Faktor yang Mempengaruhi Knowledge Sharing dalam Implementasi E learning - Meylasari, Upik Selly; Qamari, Ika Nurul (Universitas Muhammadiyah Yogyakarta, 2017)
Sharing knowledge is a core value in the learning process of higher education.This research aims to analyze the factors influence knowledge sharing in the implementation of e-learning in Universitas Muhammadiyah Yogyakarta. The subject in this study is 115 lectures in Universitas Muhammadiyah Yogyakarta. Sampling using non-probability sampling with purposive sampling type. The analytical method used is multiple linear regression analysis and using validity, reliability test, classic assumption test, F test and t test. The results of this study indicate, first, that the lecturer attitude, motivation to share, communication and technology simultaneously significant effect on knowledge sharing. Second, the lecturer attitude have a negative influence and no significant evidenced by the coefficient value of the lecturer attitude is -0.164. Another variables have a positive impact and significant, regression coefficient evidenced by the value of the motivation to share is 0,482, regression coefficient value of the communication is 0.191 and regression coefficient of technology is 0.220. Analysis of the coefficient of determination shows 0,403; which means the lecturer attitude, motivation to share, communication and technology affect knowledge sharing by 40,3%.